2014
DOI: 10.5414/cp201965
|View full text |Cite
|
Sign up to set email alerts
|

Safety of blood reinfusion after local infiltration analgesia with ropivacaine in total knee arthroplasty

Abstract: The combination of LIA and reinfusion presented herein are considered safe. However, differences in pain protocol lead to changes in the safety evaluation. Compared with previous studies, the technique of administration is of greater importance for the effect on unbound ropivacaine because of unknown mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Another study combined 375 mg ropivacaine with epinephrine as LIA with two infusion catheters, both infusing 40 mg/h. 15 Patients reached the maximum unbound ropivacaine concentration 6 h after ropivacaine injection, however, maximum total plasma concentrations were reached 24 h after the end of surgery. Despite the additional 192 mg administrated via both catheters, maximum total and unbound ropivacaine concentrations were slightly lower (0.888 lg/ml (0.539-1689) and 0.050 lg/ml (0.025-0.105), respectively) as compared to our study, which could be explained by the surgical drain.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study combined 375 mg ropivacaine with epinephrine as LIA with two infusion catheters, both infusing 40 mg/h. 15 Patients reached the maximum unbound ropivacaine concentration 6 h after ropivacaine injection, however, maximum total plasma concentrations were reached 24 h after the end of surgery. Despite the additional 192 mg administrated via both catheters, maximum total and unbound ropivacaine concentrations were slightly lower (0.888 lg/ml (0.539-1689) and 0.050 lg/ml (0.025-0.105), respectively) as compared to our study, which could be explained by the surgical drain.…”
Section: Discussionmentioning
confidence: 87%
“…Brydone et al and Ng et al 16 found a T max of 30 min after LIA resp. intra-articular administration of ropivacaine without epinephrine, while Thomassen et al 15 and Affas et al 13 found the T max 4-6 h after the administration of LIA with added epinephrine. These two latter studies encountered the same problem of 'missing' peak plasma concentrations in the sampling scheme.…”
Section: Discussionmentioning
confidence: 97%
“…[9][10][11]16 Although these technical differences may affect the pharmacokinetic profile, and differences in ropivacaine dose make a comparison of maximum concentrations problematic, the available pharmacokinetic data have shown that ropivacaine concentrations do not reach toxic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Changes were observed in perioperative management of THA and TKA patients. From the patient data, it appeared that the proportion of patients treated with LIA (a drug locally injected to reduce postoperative pain and to accelerate recovery [ 44 46 ]) increased in control hospitals from 21.3 to 40.8% and in intervention hospitals from 20.1 to 32.9%. Several physicians in the intervention hospitals mentioned during the interactive education and educational outreach visit that they hesitate to use both LIA and postoperative blood salvage to avoid drainage of the LIA and to avoid systemic effects by reinfusion of the LIA.…”
Section: Resultsmentioning
confidence: 99%
“…This study is the first to suggest that substitution of low-value care may encourage de-implementation. In this study the substitutes were TXA, a simple, safe, and inexpensive blood-sparing technique [ 47 ] and LIA, a technique aimed at pain relief, which is found difficult to combine with blood salvage, as the blood salvage drain directly drains the analgesic fluid [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%